Comparative safety profile of tyrosine kinase inhibitors in NSCLC: a network meta-analysis of hypertension and thrombotic risks - Tan, Mingming; Pu, Chenwei; Wang, Zhenzhen; Jin, Chengwei (Frontiers in Pharmacology, 2025)
BackgroundThis study examines the risks of hypertension and thrombotic events in NSCLC patients treated with Tyrosine Kinase Inhibitors (TKIs).ObjectiveTo compare the safety profiles of TKIs used in NSCLC treatment, focusing on hypertension and thrombotic risks.MethodsA comprehensive search identified randomized controlled trials evaluating the effects of TKIs in NSCLC patients. Bayesian network meta-analysis was employed to construct a comparative network of treatments.ResultsThirty studies involving 11,375 patients were included. Erlotinib had the lowest incidence of hypertension (SUCRA: 91.1%), followed by chemotherapy (88.8%). For thrombotic events, Erlotinib had the lowest risk (SUCRA: 66.1%), while Anlotinib and Cabozantinib had the highest thrombotic risks (SUCRA: 26.9%).ConclusionErlotinib presents the lowest risk for hypertension and thrombotic events, making it a preferred choice for NSCLC patients with cardiovascular concerns.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024530770.